Análise e Monitorização do Desempenho do Serviço de Arquivo do Centro Hospitalar Universitário de São João - Teresa Alexandra Magalhães Campos (2022)
The complexity inherent to the organization of a hospital entity and the increase in information technology capabilities place increased demands on hospital information management. The ability to evaluate the performance of the main actors of this function is a prerequisite for an informed decision making. This study aims to identify a set of indicators for monitoring the performance of an information service in a hospital context, using as a case study the Archive Service of the Centro Hospitalar Universitário de São João (CHUSJ). The method used is based on the analysis of the main organizational processes of the Service, to which absolute and relative indicators are associated. The indicators selected are those that highlight the evolution of the activity and the impact of the management measures taken. The model of indicators obtained is applied in two moments, before and after a significant change in the organizational processes, constituted by the implementation of the Digital Clinical Repository at the CHUSJ.